Determination of Preservative Levels of Sodium Benzoate in Packaged Mayonnaise UV-Vis Spectrophotometry as an Effort to Improve Practice Experience Basic Chemistry Course Students - Lidya Wati; Muhammad Nazar; Fadli Syahputra (JURNAL SERAMBI ILMU, 2022)
Sodium benzoate is the sodium salt of benzoic acid which is often used inprocessed foods and beverages, According to the regulation of the Head ofBPOM RI No. 36 of 2013, this preservative is permitted in its use but has alimit on the use of mayonnaise, which is 1000 mg/kg body weight. Thepurpose of this study was to determine the content of sodium benzoate andthe levels in packaged mayonnaise. This research was conducted at theChemistry Laboratory of the Faculty of Teacher Training and Education,Syiah Kuala University, Banda Aceh to improve the student learningexperience in basic chemistry courses, using five samples of packagedmayonnaise. The results showed that the five samples of packagedmayonnaise were positive for the preservative sodium benzoate.Determination of the preservative content of Sodium benzoate wasdetermined using UV-Vis spectrophotometry method at max 280 nm. Fromthe measurement results, the sodium benzoate content of sample M1 = 68mg/kg, sample M2 = 35.5 mg/kg, sample M3 = 85.5 mg/kg, sample M4 =95.5 mg/kg and M5 mg/kg = 30.5 and the use of preservative sodiumbenzoate in the packaged mayonnaise does not exceed the maximum limitthat has been set.